1985
DOI: 10.1007/bf01000750
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback control of migraine headaches: A comparison of two approaches

Abstract: In order to assess the relative effectiveness of finger warming and temporal blood volume pulse reduction biofeedback in the treatment of migraine, 22 female migraine patients were assigned to one of three experimental conditions: temporal artery constriction feedback, finger temperature feedback, or waiting list. Biofeedback training consisted of 12 sessions over a 6-week period. All patients completed 5 weeks of daily self-monitoring of headache activity (frequency, duration, and intensity) and medication be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…4 In fact, patients who undergo biofeedback are often urged to apply their training at the earliest sign of a headache onset. [5][6][7][8][9][10] Although the belief in question is consistent with some clinical observations made by Stroebel & Glueck, 11 it should be pointed out that it has never been submitted to any kind of empirical testing. Consequently, a question arises as to whether or not biofeedback researchers and clinicians should go on putting so much emphasis on the early application of biofeedback strategies to control migraine headaches.…”
supporting
confidence: 54%
“…4 In fact, patients who undergo biofeedback are often urged to apply their training at the earliest sign of a headache onset. [5][6][7][8][9][10] Although the belief in question is consistent with some clinical observations made by Stroebel & Glueck, 11 it should be pointed out that it has never been submitted to any kind of empirical testing. Consequently, a question arises as to whether or not biofeedback researchers and clinicians should go on putting so much emphasis on the early application of biofeedback strategies to control migraine headaches.…”
supporting
confidence: 54%
“…The inclusion and the exclusion criteria(s) used originally to determine whether or not those patients were suffering from migraine headaches are described elsewhere. [10][11][12][13][14] Treatment. The biofeedback treatment consisted of either finger temperature or temporal blood volume pulse (BVP) biofeedback, two procedures that have been shown to be equally effective in the treatment of migraine headaches.…”
Section: Methodsmentioning
confidence: 99%
“…Quite some time ago, Anderson et al [12] found six sessions of hypnotherapy to be superior to a prophylactic treatment with prochlorperazine (20 mg/d for 1 year), a therapy that would not be used today. Gauthier et al [13] compared self-hypnosis with a combination of TBF and relaxation and did not find any significant difference. In contrast to acupuncture, there is no such thing as sham hypnosis, which makes it almost impossible to control for nonspecific effects of this therapy.…”
Section: Hypnosismentioning
confidence: 97%